Behaviors Applying Health Protocols to Breastfeeding Mothers Who Have Been Vaccinated and Who Have Not Been Vaccinated Covid-19 - Ulfatul Latifah; Riska Arsita (JURNAL KEBIDANAN, 2021)
In Indonesia, covid-19 through middle December 2020, there are over 600 thousand confirmed cases with a death toll over 16 thousand. Some of Indonesia's covid-19 pandemic efforts include prevention measures with the application of health protocols such as walking distance, washing your hands with soap and wearing a mask, vaccinating covid-19, and 3t (tests, calls, follow-up). The purpose of this research is to determine behavioural differences of health protocol at mothers breast-feeding that have been and have not been given from the covid19 vaccination. The study was conducted online through Google form in the Margadana city of Tegal, with the subjects of this study are 42 breastfeeding mothers with purposive sampling techniques. This research was quantitative which used observational with the cross sectional approach. The statistical test used by Mc Nemar to identify the difference in behavior implementing health protocols to breastfeeding mothers who have been vaccinated and who have not been vaccinated covid-19. The finding shows there was a behavioral difference in the application of the 3M health protocol on the mothers breast-feeding who had been vaccinated and had not been vaccinated covid-19 with exact sig values. It is expected that the city's government will be even more firm to sanction communities that violate the health protocol in countermeasure covid-19.